Immunosuppressive potential of human amnion epithelial cells in the treatment of experimental autoimmune encephalomyelitis - McDonald, Courtney A. (J Neuroinflammation, 2015)
BACKGROUND: Multiple sclerosis (MS) is an autoimmune inflammatory disease of the central nervous system (CNS). In recent years, it has been found that cells such as human amnion epithelial cells (hAECs) have the ability to modulate immune responses in vitro and in vivo and can differentiate into multiple cell lineages. Accordingly, we investigated the immunoregulatory effects of hAECs as a potential therapy in an MS-like disease, EAE (experimental autoimmune encephalomyelitis), in mice. METHODS: Using flow cytometry, the phenotypic profile of hAECs from different donors was assessed. The immunomodulatory properties of hAECs were examined in vitro using antigen-specific and one-way mixed lymphocyte proliferation assays. The therapeutic efficacy of hAECs was examined using a relapsing-remitting model of EAE in NOD/Lt mice. T cell responsiveness, cytokine secretion, T regulatory, and T helper cell phenotype were determined in the peripheral lymphoid organs and CNS of these animals. RESULTS: In vitro, hAECs suppressed both specific and non-specific T cell proliferation, decreased pro-inflammatory cytokine production, and inhibited the activation of stimulated T cells. Furthermore, T cells retained their naïve phenotype when co-cultured with hAECs. In vivo studies revealed that hAECs not only suppressed the development of EAE but also prevented disease relapse in these mice. T cell responses and production of the pro-inflammatory cytokine interleukin (IL)-17A were reduced in hAEC-treated mice, and this was coupled with a significant increase in the number of peripheral T regulatory cells and naïve CD4+ T cells. Furthermore, increased proportions of Th2 cells in the peripheral lymphoid organs and within the CNS were observed. CONCLUSION: The therapeutic effect of hAECs is in part mediated by inducing an anti-inflammatory response within the CNS, demonstrating that hAECs hold promise for the treatment of autoimmune diseases like MS.